Comparison of the Morphological Structure of Pollen in Five Provenances of Gyrinops versteegii (Thymelaeaceae) in Lombok - Rukmana, Sukma; Mulyaningsih, Tri; Muspiah, Aida (Universitas PGRI Palembang, 2024)
Gyrinops versteegii (Thymelaeaceae) is one of the agarwood-producing trees originating from Lombok, there are five provenances, namely Pantai, Madu, Buaya, Soyun, and Beringin. This study aims to compare the morphological structure of pollen in five provenances of G. versteegii in Lombok. The method of sampling and data analyzes were used random sampling and descriptive. Samples were taken from West Lombok: Sidemen Village (Pantai), North Lombok: Menggala Village (Buaya), Gangga Village (Beringin), Central Lombok: Taman Baru Village (Madu), and Soyun from Karang Pule Village, Mataram. The study parameters were pollen diameter and pollen morphology: shape, aperture, and sculpture. The results showed that the size of pollen from Buaya was wider than that from Madu, Beringin and Pantai. Based on the length of the polar axis/equatorial diameter, Buaya Provenance, Beringin and Pantai pollen are round in shape, and Madu Provenance is subprolate in shape. The Buaya, Madu and Beringin provenances have a monocolpate opening type, and the Periporate type for the Pantai provenance.